2017
DOI: 10.1111/jocn.13748
|View full text |Cite
|
Sign up to set email alerts
|

Defining and comparing learning actions in two simulation modalities: students training on a latex arm and each other's arms

Abstract: This study suggest that student nurses may be differently and inadequately prepared in peripheral vein cannulation in two simulation modalities used in the academic setting; training on a latex arm and on each other's arms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 44 publications
1
41
0
Order By: Relevance
“…On the one hand, the students worked together in pairs during the virtual simulation sessions, which allowed for discussion and promoted learning [21]. On the other hand, the results demonstrated that some of the students participating in the study did not find the virtual simulation to be educational.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the students worked together in pairs during the virtual simulation sessions, which allowed for discussion and promoted learning [21]. On the other hand, the results demonstrated that some of the students participating in the study did not find the virtual simulation to be educational.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies on the effects of peer learning for nurses in simulation centres and clinics (see e.g. Christiansen and Bell, 2010;Christiansen et al, 2011;Williams and West, 2012), but few have examined peer learning between students at the same level in a simulation centre (McKenna and French, 2011;Ravik et al, 2017;Strand et al, 2009), as in this study. Students are usually less stressed and more relaxed in learning situations where fellow students provide feedback (Owens and Walden, 2001;Rush et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…When students take over much of the feedback function, they need to have some of the same knowledge as the teacher, although they are not expected to reach a teacher's level of knowledge (Hattie and Timperley, 2007). Without teacher guidance, errors may not be detected and corrected (Ravik et al, 2015(Ravik et al, , 2017. Teachers have an important role in bridging the gap between current and desired performance, which is best achieved by correcting errors (Gamlem and Smith, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This exploration may in turn afford an understanding of challenges that students encounter in their learning processes in the clinical setting and can form a basis for improving students' practical skill learning during their clinical placement. In previously published articles from the larger study, we have reported on transfer of skill learning (PVC) from simulation to the clinical setting [ 9 ] and learning actions that students were engaged in during simulation-based PVC learning [ 35 ]. Because of challenges found in the previous studies related to learning and performances of the technical implementation of the vein cannula, we have in the current research explored conditions influencing students learning and performances of this particularly part of the skill during a clinical placement period.…”
Section: Introductionmentioning
confidence: 99%